РОЛЬ ДИДАКТИЧНИХ ТЕХНОЛОГІЙ В ПРОЦЕСІ ФОРМУВАННЯ ПРОФЕСІЙНО ВАЖЛИВИХ ЯКОСТЕЙ МАЙБУТНІХ СОЦІОЛОГІВ (Педагогіка вищої та середньої школи, 2022)
In this article the special attention is paid to the necessity of innovative didactics technologies me in the process of professionally important qualities of future sociologists formation.